Pengaruh Kecerdasan Spritual terhadap Aktivitas Belajar Siswa Kelas VII pada Mata Pelajaran PAI di SMP PGRI 5 Kota Bogor - Syahrul Nur Rohman Pratama; Mulyadi Kosim; Nirwan Syafrin (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
Spiritual intelligence is the sharpness of thinking and understanding of reason and conscience in managing and utilizing meanings, values ​​and quality in life, both in solving problems or making decisions, behaving with fellow humans and the natural environment based on the principle of only to Allah. Then learning activities are activities or activities carried out by students which are expected to be useful activities related to teaching and learning activities. This study aims to determine the description of the spiritual intelligence of students at SMP PGRI 5 Bogor City. to find out the description of student learning activity in PAI subjects at SMP PGRI 5 Bogor City, to describe the effect of spiritual intelligence on student learning activities in PAI subjects at SMP PGRI 5 Bogor City. This type of research uses quantitative research is research that is taken through a number (numeric) count. Data collection techniques in this study using questionnaires, documentation, observation. Data analysis used simple linear regression with a significance level of 5%. When viewed from the acquisition of Tcount = 6.946 Ttable = 1.676. And the significance value of 0.000 is smaller than 0.05 (0.000 <0.05) meaning that there is a positive and significant influence of spiritual intelligence on learning activities. Judging from the calculation of R square = 0.501 which means that spiritual intelligence affects the learning activities of class VII students in PAI subjects at SMP PGRI 5 Bogor City by 50.1% and the remaining 49.9% is influenced by other factors.